The impact of foreign direct investment (FDI) and remittances on economic growth in the SADC Region - Mushori, Roosevelt (Graduate School of Business (GSB), 2026)
Emerging economies across the globe are faced with a gap between savings and investment needed to grow their economies. Thus, in recent years, Foreign Direct Investment (FDI) and Remittances have been identified as key sources of financing to bridge this gap. The study investigates the impact of Foreign Direct Investment (FDI) and remittances on economic growth in 16 Southern African Development Community (SADC) member states between 2010 and 2022. Using the Generalised Method of Moments (GMM) analysis, the study finds that the effect of FDI on economic growth in the region is statistically insignificant, whereas remittances have a negative impact on economic growth in both the short- and long-run. The findings also suggest that FDI and remittances have a weak substitutive relationship, rather than being complementary to each other interactively. These findings thus indicate that FDI and remittances do not promote economic growth in the SADC region.